Patient Safety Framework in Healthcare Regulatory System of Nepal: A Call for Action - Satish Kumar Deo; Srijana Shakya; Sujaya Gupta (Journal of Nepal Medical Association)
Patient safety in Nepal’s healthcare system remains a critical challenge due to fragmented regulatory frameworks, resource constraints, and inadequate monitoring mechanisms. Despite multiple regulatory bodies overseeing healthcare services, their lack of coordination limits effectiveness. Learning from international models, Nepal can enhance patient safety by establishing a unified governance system, strengthened monitoring mechanisms, and increased budget allocations. A